Exchange Rate Fluctuations and Their Impact on Inflation: An Analysis Using National Data - Diana Magfiroh (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background:Exchange rate fluctuations pose a critical challenge for modern economies, particularly in a globalized financial environment. The relationship between exchange rates and inflation is a key concern for policymakers, central banks, and economic researchers, as fluctuations in exchange rates can significantly influence domestic price levels and overall economic stability.Objective:This study aims to analyze the dynamic relationship between exchange rate fluctuations and inflation, focusing on the magnitude, asymmetries, and long-term effects of exchange rate pass-through to inflation in national economies. The goal is to better understand how exchange rate movements impact inflation and inform policy responses.Method:The research employs a quantitative approach using time series econometric analysis, specifically the Autoregressive Distributed Lag (ARDL) bounds testing method. Data were collected from national macroeconomic indicators for the period of 2005–2024.Findings and Implications:The findings reveal that exchange rate fluctuations have a significant pass-through effect on inflation. A 10% depreciation in the exchange rate leads to a 3.42% increase in inflation. Asymmetric effects were observed, where depreciation causes larger inflationary pressures than appreciation. These results emphasize the importance of incorporating exchange rate movements into inflation forecasting and policymaking, especially for countries with significant import dependencies.Conclusion:The study highlights the critical role of exchange rate fluctuations in inflation dynamics and underscores the need for policymakers to incorporate exchange rate movements into their inflation forecasting models and macroeconomic strategies. Future research should explore sector-specific impacts and consider the influence of global economic conditions in shaping the exchange rate-inflation relationship.